2015
DOI: 10.1371/journal.pone.0126247
|View full text |Cite
|
Sign up to set email alerts
|

Is Ambient Light during the High Arctic Polar Night Sufficient to Act as a Visual Cue for Zooplankton?

Abstract: The light regime is an ecologically important factor in pelagic habitats, influencing a range of biological processes. However, the availability and importance of light to these processes in high Arctic zooplankton communities during periods of 'complete' darkness (polar night) are poorly studied. Here we characterized the ambient light regime throughout the diel cycle during the high Arctic polar night, and ask whether visual systems of Arctic zooplankton can detect the low levels of irradiance available at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 47 publications
1
67
0
Order By: Relevance
“…Thus, rates of growth, respiration, and reproduction for the examined benthic organisms were not lower during the polar night compared to other times of the year. In addition, measurements of a potential circadian cycle (24 hr) in both Chlamys islandica valve opening and vertical migration of zooplankton indicated that, despite 4 months of apparent darkness, activity cycles remain entrained to the existing but weak diurnal cycles [34] and cues (Table S1). …”
Section: Benthic Communitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, rates of growth, respiration, and reproduction for the examined benthic organisms were not lower during the polar night compared to other times of the year. In addition, measurements of a potential circadian cycle (24 hr) in both Chlamys islandica valve opening and vertical migration of zooplankton indicated that, despite 4 months of apparent darkness, activity cycles remain entrained to the existing but weak diurnal cycles [34] and cues (Table S1). …”
Section: Benthic Communitiesmentioning
confidence: 99%
“…Irradiance (E) is extremely low during the winter polar night period [34], resulting in primary production rates close to zero [41] and in little newly produced food for pelagic and benthic grazers [42]. Low E is also assumed to hamper feeding by visual predators over much of the water column, including zooplankton, fishes, and seabirds [34,43].…”
Section: Outlook and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cronin et al, 2016), that can be particularly important during the Arctic winter. Recently published work from this region show that some organisms respond to even very weak variations in light level, and mass-vertical migration during Arctic winter driven by moonlight has been documented (Cohen et al, 2015;Last et al, 2016). However, these studies have focused on zooplankton in the upper 50 m.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to other seasons when atmospheric light is present for some or all of the diel period, the winter light field33 would provide far less interference with the production and perception of bioluminescence. The high Arctic during polar night was once understood to be biologically dormant until light and the spring bloom recovered the system with organic carbon through photosynthesis.…”
mentioning
confidence: 98%